PERANCANGAN SISTEM PELAYANAN RESTORAN BERBASIS WEB MOBILE MENGGUNAKAN FRAMEWORK YII2 - Maharani Hamidah; Geovanne Farell (Jurnal Teknologi Informasi dan Pendidikan, 2019)
The increased business needs and rapid technological developments helped to make easier in marketing, ordering, or delivery. Restaurant service that is still manual is only efficient for visitors who are few. With a-based restaurant application it mobile web will make it easier and more efficient for large restaurants with more visitors. With reliable Smartphone, visitors immediately place an order through the waterfall method and database MySQL, so that later it will produce an application that is accessed via a Smartphone customer in handling food menu orders.